Impact of Physical Activity on Alzheimer’s Disease: A Randomised Controlled Study - Claire, Toulotte; Isabelle, Caby; Hélène, Olivier; Nicolas, Olivier (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
Purpose: To study the effects of physical training on behavior and balance issues in elderly people afflicted with Alzheimer’s disease. Method: Forty patients (average age: 80 years old) participated in the study. The individuals were placed into two groups: a control group, which did not participate in any kind of training, and a trained group, which followed an eight-week training program. The training program comprised 2–3 sessions of light physical activity or walking per week; each session had an average duration of 15–55 min. Before (T1) and after (T2) the training program, an assessment of the psychical, psychological, physical, and functional parameters was conducted. Results: Upon completion of the physical training program, there was a significant (p < 0.05) improvement in the Tinetti test (T1: 19.5 ± 4.2 s; T2: 20.1 ± 4.1 s), a significant decrease in the completion time of the “get up and go” track for all of the participants (T1: 23.1 ± 8.1 s; T2: 19.5 ± 6.1 s), and a significant reduction in the seriousness of the behavioral issues observed. Conclusion: This preliminary study revealed that physical training had an overall beneficial impact on Alzheimer’s patients, especially on their behavior and balance.